Caracterização e aproveitamento de água cinza para uso não-potável em edificações - Bazzarella, Bianca Barcellos (2005)
Alternative sources of residential water supply may aid water conservation. One example is the reuse of greywater for non potable purposes (car washing, garden irrigation and toilet flushing). This work investigates alternatives for reducing potable water consumption and the production of wastewater in buildings, using greywater treatment applied to toilet flushing. Initially, a physical-chemical and microbiological qualitative characterization of greywater collected in several sources (lavatory, shower, kitchen sink, tank and wash machine) was carried out. The greywater presented significant concentrations of quickly biodegradable organic substances and sulphates, highlighting its high potential for H2S production when stored untreated. The nutrient concentrations (N and P) were minor compared with the ones in a conventional sewer, since they largely came from faeces and urine. The presence of E. coli showed the need for disinfection before reuse, depending on the quality standards for toilet flushing. Additionally a reuse system was monitored in a building at UFES University. The building contains two professors rooms with individual bathrooms and collective bathrooms, male and female, giving a total of six lavatories, two showers, six toilets and two urinals. This building s greywater (the effluent of showers and lavatories) is directed to a Greywater Treatment Plant (ETAC), whose processing is based on a combination of techniques - Compartment Anaerobic Reactor (RAC), Submerged Aerated Filter (FBAS), Tertiary Filter (FT) and disinfection based in chlorine. The adopted treatment showed high efficiency in the removal of turbidity, color, BOD5, QOD, E. coli, and was compatible with diverse standards established for non potable reuse. The characteristics of the generated sludge of this treatment presented concentrations of ST and the relation SV/ST of 0,59% and 77% (1st chamber of the RAC), 0.54% and 74% (2nd chamber of the RAC), 0.004% and 32% (aerobic sludge), 0.008% and 60% (1st collects tertiary sludge) and 0.004% and 25% (2nd collects tertiary sludge).